An eagle in the snow - Morpurgo, Michael (Feiwel and Friends, 2017)
In 1940 England, stuck in a train tunnel while German fighter jets fly overhead, Barney hears an unlikely story of a highly decorated World War I soldier who once had a chance to kill young Adolf Hitler.